Elucidating the Role of BRCA1 in Skeletal Muscle Myogenesis and Function - Koripella, Ananya (East Carolina University, 2021)
The breast cancer 1 early onset gene (BRCA1) is a tumor suppressor gene susceptible to mutations associated with cancer development. We have identified that the BRCA1 gene is expressed in skeletal muscle and plays a critical role in regulating muscle function, in part through maintaining DNA integrity. In this project, we hypothesized that BRCA1 content is necessary for myogenesis, an essential process for skeletal muscle development and repair following injury. Development and repair of skeletal muscle is mediated by stem cells committed to the myogenic lineage (i.e. satellite cells) undergoing myogenesis. While it is understood that DNA damage is an unavoidable consequence of myogenesis, the mechanisms of satellite cell DNA repair are unknown. Here, we hypothesized that BRCA1 expression is necessary in satellite cells to repair DNA to ensure appropriate development and repair of skeletal muscle. To test this hypothesis, we employed three novel mouse models, where BRCA1 content was either overexpressed or ablated in the skeletal muscle or satellite cells. To induce myogenesis, the anterior compartment of a lower limb was injured with an injection of 1.2% BaCl2. The contralateral limb was injected with the same volume of sterile PBS. One week after injections, the skeletal muscles were removed, and the muscle quality was assessed. Myofiber size (i.e. cross-sectional area) was measured in the tibialis anterior (TA) muscles to determine the ability of the muscle to recover from injury when the satellite cells either overexpress or lack BRCA1. In addition, the number of cells with central nucleation was determined as a marker of pathology within the muscle. The data shows that the overexpression of BRCA1 in the skeletal muscle provides no improvement in skeletal muscle quality after an acute injury. However, the overexpression of BRCA1 in the satellite cells leads to larger muscle cells after the same insult and smaller muscle cells when BRCA1 expression is lost from satellite cells. In conclusion, the results suggest that a known DNA repair protein, BRCA1, is critical for satellite cell-induced repair of skeletal muscle after an acute injury.
Keywords: satellite cells; skeletal muscle myogenesis; BRCA1